Authentic Assessment in The Students as Pre-Service Teacher Education at Karangasem Public Schools: Phenomenological Study in Karangasem Regency - Ni Komang Sri Mariati (STKIP Taman Siswa Bima, 2025)
The students as pre-service teachers as the bridge for producing good quality of the future teacher. In the era of 21st century learning, the teacher and the student are need to have ability facing the problems related to real situation. Authentic assessment needs to be developed and investigate deeply related to the situation. The purposes of the research to find out the theory of practice pf teaching and the real practice of teaching that find while conducting pre-service teacher program and to investigate the implementation of authentic assessment in student as pre-service teacher. The study used qualitative design through phenomenological method. The data were analyzed by theory from Colaizzi’s method of descriptive data analysis. The study involving 64 English student as pre-service teacher in seventh semester at STKIP Agama Hindu Amlapura. The study uses purposive sampling in choosing the respondents. The study conducting at Karangasem Public schools. The result from the study was there are 3 major gaps in process teaching such as, diversity of students in making lesson plan, learning media, and classroom management. Next, the study found that mostly pre-service teacher conducts their practice with implementing authentic assessment. But, some of the pre-service teacher still use traditional assessment because the material that they taught just for remembering not for understanding. The authentic assessment could use in 21st learning century but some sub topic need use traditional assessment.